The Role of Corporate Workplace Inclusivity Policies, Brand Equity, and Innovation Intensity in Firm Profitability: A Moderated Mediational Approach - Rahman, M.; Rodríguez-Serrano, M.Á.; Shimul, Anwar Sadat; Faroque, A.R. (2023)
Firms are increasingly adopting pro-lesbian, -gay, -bisexual, -transgender, inclusivity and diversity (LGBT-ID) policies for workforce management. This study develops a parsimonious, albeit complex, moderated-mediated framework by employing a panel dataset combining data from archival sources and involving a sample of predominantly large and publicly held firms from the USA between 2002 and 2018. The number of observations varied across variables with a minimum of 414 observations (corporate brand equity) and a maximum of 3,566 observations (self-reported LGBT-ID policy). This treatise demonstrates that adopting LGBT-ID policies positively impacts firms’ profitability. Moreover, pro-LGBT-ID policies during this specific period have a positive effect on corporate brand equity, which in turn affects firm profitability, indicating that brand equity plays a mediating role in the nexus between pro-LGBT-ID policies and firms’ financial performance. Furthermore, innovation intensity strengthens the relationship between pro-LGBT-ID policies and brand equity during the sample period of the study.